Stress Relief and Stimulation of Coal Reservoir by Hydraulic Slotting - Xiaoyang Cheng; Qinghua Zhang; Zhigang Zhang; Yunlong Zou; Guo Junjie (Advances in Civil Engineering)
Coal seam permeability is one of the key factors influencing the gas extraction efficiency, which is of great significance to reduce coal and gas dynamic disasters in gassy coal mines. Hydraulic slotting technique is an effective method to stimulate the coal reservoir, but the selection of slotting key parameters has great impact on gas extraction efficiency. For this reason, the hydraulic slotting model was established by using FLAC3D software to analyze the stress distribution before and after slotting. Then, the influence of borehole diameter, slotting width, and slotting length on coal seam stress relief is also discussed. The results show that the slotting width has a great influence on the stress relief of the coal seam, while the borehole diameter and slotting length have no obvious influence on that. Based on the results of numerical simulation, field tests were carried out in Sangshuping NO.2 coal mine. The results show that the coal seam stress can be fully released, resulting in the improvement of coal seam permeability. The gas extraction efficiency can be highly enhanced by hydraulic slotting. This research achievement provides the guidance basis for high-stress water jet slotting technology with adaptive selection of slotting parameters in different geological conditions.